Report of the Working Group of the Planning Commission on Modernisation of Library Services and Informatics for the Seventh Five Year Plan 1985—90 - Planning Commission (Planning Commission, 1984)
The Planning Commission vide their office memorandum No 12011/3/83- Edn. of Nov. 17, 1983 set up a Working Group on Modernization of Library Services and Informatics for the 7th Five Year Plan (1985-90) with the following terms of reference : To take stock of the position in respect of library services and informatics as is likely to be reached by the end of 1984-85, to Identify problem areas and suggest remedial measures; To suggest feasible perspective of development of library services and Informatics upto 2000 A.D. Particularly with a view to equalising these facilities to all sections of the people and to enable the national library and Informatics system make Its maximum contribution to the development of a modern society.
Planning Commission